Circuítos curtos como estratégia de manutenção da agricultura camponesa: o caso da feira agroecológica de Mossoró-RN - Maia, Zildenice Matias Guedes (2018)
Agroecological fairs are spaces for strengthening family farming and for (re) appreciation of food by a diversity of actors, including farmers, farmers and consumers. In this sense, different social groups promote changes in the production and food consumption systems that, in turn, make possible the reconfiguration of rural spaces, and promote in the urban space a diversity of access to organic food. The research was based on the hypothesis that agroecological fairs, besides an important role in guaranteeing the food security of producers and consumers, and the valorisation of traditional and cultural knowledge, has led to a reconfiguration of the spaces where these practices are given. The objective of the research was to understand the extent to which agroecological fairs as short marketing channels are forged as strategies for the construction and maintenance of a sustainable agriculture model capable of contributing to the food security of farmers, consumers and at the same time put new forms of food production and consumption into action.The research was a qualitative approach and the study had as an empirical reference the experience of the Association of Agroecological Producers and Producers of Mossoró-RN, composed of farmers from thirteen settlements and rural communities in the State of Rio Grande do Norte. The data were collected through interviews in the production spaces with the farmers, and with the consumers of APROFAM. The performance of this social group has promoted significant changes in food production and consumption systems, and in this sense, agroecology constitutes a broad set of initiatives that strengthen and promote the resignification of family agriculture for these actors. For farmers to adopt agroecological production was representative for the food and nutrition security of their families, because they have variety and quality in their tables; besides the aspect of food sovereignty, since for many, most of the food they eat comes from their backyards. For consumers, the consumption of this food also has significance. For these, the agroecological fair has enabled access to a food that among other characteristics, presents greater durability, flavor and smell that differs from foods found in conventional markets. In addition to consuming this food, consider that they are valuing the regional food culture, in addition to promoting the valuation of family farming. And thus, they strengthen reciprocity and autonomy in this alternative agri-food market, consolidating its permanence. However, for some consumers, this relationship in some respects still constitutes fragile, and may be absent for some, the condition of politicized or even reflexive consumption.